Critical Incidents for Hispanic Students on the Path to the STEM Doctorate - Horton, Dawn; Torres-Catanach, Irma (Frontiers in Psychology, 2022)
Hispanics are grossly underrepresented in the receipt of STEM Ph.Ds. The National Science Foundation (NSF) Science and Engineering Indicators (Trapani & Hale, 2019) suggest that only 7.8% of S & E doctoral recipients are Hispanic while their representation in the population is more than twice that, and that figure goes even higher if restricted to those within the college-age range. To address this gap, NSF has awarded a grant (the Hispanic Alliance for Graduate Education and the Professoriate, H-AGEP) to the City College of New York and the University of El Paso, Texas to work with Hispanic STEM doctoral students to provide teaching training and preparation for academic positions so they can become role models for Hispanic community college undergraduates. In working to understand the career-decision making of our Fellows, in-depth interviews were conducted (n=13) to understand what put them on the path to defy the odds and become a STEM doctoral recipient. Interview results suggest that isolated, critical incidents and chance events were responsible for a number of our students entering into doctoral programs. These seemingly chance events suggest that the path for many Hispanic STEM doctoral students is not one that is assured from a young age and rather that Hispanic undergraduates may benefit from more “planned” critical incidents that would support their pursuit of the Ph.D. in STEM.